ENGINEERING OF UNIVERSITY INTELLIGENT LEARNING SYSTEMS - Vasiliy M. Trembach (Статистика и экономика)
In the article issues of engineering intelligent tutoring systems of University with adaptation are considered. The article also dwells on some modern approaches to engineering of information systems. It shows the role of engineering e-learning devices (systems) in system engineering. The article describes the basic principles of system engineering and these principles are expanded regarding to intelligent information systems. The structure of intelligent learning systems with adaptation of the individual learning environments based on services is represented in the article.